Polarization of Judge Considerations in Waqf Disputes at Aceh's Syar'iyah Cour - Abdullah, Arifin; Sholihin, Riadhus; Habibi, Muhammad (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2023)
To protect waqf property, the Waqaf Law and KHI demand that waqf conflicts be settled peacefully to reach a win-win solution. However, Sharia Court judges still frequently decide waqf disputes in Aceh with a win-lose outcome; as a result, they do not protect waqf assets. This study evaluates Indonesian normative law using a qualitative method and court rulings. Field and library research yielded primary, secondary, and tertiary data. The study discovered three models of waqf conflicts in the Syar'iyah Court: waqf disputes that look at the parties' positions, which influences court evidence; waqf disputes that look at movable and immovable waqf assets; and models that look at both. Waqf property is either productive or unproductive. Second, the parties' reasons for settling the Waqf Dispute at Syar'iyah Court were: 1) Peace and 2) Interest factors to achieve legal certainty. Third, Syar'iyah Court judges only assess events, legal facts, and evidence in dispute settlement, not waqf asset protection. This research hopes to give Syar'iyah Court judges a legal umbrella to actively resolve waqf conflicts.Untuk melindungi harta benda wakaf, UU Waqaf dan KHI menuntut agar konflik wakaf diselesaikan secara damai untuk mencapai win-win solution. Namun, hakim Mahkamah Syariah masih sering memutuskan sengketa wakaf di Aceh dengan hasil menang-kalah; akibatnya, mereka tidak melindungi aset wakaf. Studi ini mengevaluasi hukum normatif Indonesia dengan menggunakan metode kualitatif dan putusan pengadilan. Penelitian lapangan dan kepustakaan menghasilkan data primer, sekunder, dan tersier. Studi ini menemukan tiga model konflik wakaf di Mahkamah Syar'iyah: sengketa wakaf yang melihat posisi para pihak, yang mempengaruhi pembuktian di pengadilan; sengketa wakaf yang menyangkut harta benda wakaf bergerak dan tidak bergerak; dan model yang melihat keduanya. Harta wakaf bisa produktif atau tidak produktif. Kedua, alasan para pihak menyelesaikan Sengketa Wakaf di Mahkamah Syar'iyah adalah: 1) Perdamaian dan 2) Faktor kepentingan untuk mencapai kepastian hukum. Ketiga, hakim Mahkamah Syar'iyah hanya menilai peristiwa, fakta hukum, dan bukti dalam penyelesaian sengketa, bukan perlindungan harta benda wakaf. Penelitian ini diharapkan dapat memberikan payung hukum kepada hakim Mahkamah Syar'iyah untuk secara aktif menyelesaikan konflik wakaf.